(untitled) (International Journal of Management and Sustainability, 2014)
This article seeks to determine the critical success factors for franchised restaurants entering the Kenyan market from the customers’ perspective. We used a quantitative methodology by taking a survey. The respondents were identified using convenience sampling. A sample of 389 franchised restaurant customers was drawn and a response rate of 98.7% was obtained. It is suggested that the critical success factors for franchised restaurants from customers’ perspective include good and consistent products and product range (menu mix), competent staff who were clean, warm, courteous and welcoming, a pleasant and clean atmosphere, reasonable and stable prices of products and a convenient location with efficient service. This paper has added value in theory by identifying the critical success factors for franchised restaurants entering the Kenyan market from customers’ perspective. The findings can be used by restaurant franchises that seek to establish successful businesses in the Kenyan market and other similar regional markets.